Aplikasi Pengontrolan Kelembaban Tanah pada Smart Garden Menggunakan Sensor Soil Moisture - Faridah Faridah (Universitas Negeri Gorontalo, 2019)
The problem of stabilizing soil moisture can be addressed by designing a soil moisture control application that serves to provide information on soil moisture conditions within a certain time period in the form of an order to water and stop watering. The research aims to carry out a sensing simulation on Soil Moisture Control Application in Smart Garden using Soil Moisture Sensor. This research is an experimental research of tool design in order to improve the quality and working system of the tool. The results of this study indicate that the device will function or not If the sensor detects that the ground is dry or the measurement results are brought to 50%, then the sensor will respond and send a signal to the microcontroller to activate the relay so that the pump will turn on automatically. If the device does not function then we can do it automatically manually by controlling it via a smartphone application. When the soil reaches a soil moisture level above 50% from the results of either watering done by the tool or from the rain detected by the soil mousture sensor then the tool will stop automatically and the tool will return to function when the soil returns dry, so that it can control soil moisture. This tool is equipped with indicators using LED lights when the tool is functioning.